m(6)A RNA甲基化在非小细胞肺癌中的研究进展 (Zhongguo Fei Ai Za Zhi, 2020)
N(6)-methyladenosine is one of the most prevalent mRNA modification in eukaryotes. The regulation of this pervasive mark is a dynamic and reversible process. m(6)A RNA methylation is catalyzed by m(6)A writers, removed by m(6)A erasers and recognized by m(6)A readers, thereby regulating multiple RNA processes including alternative splicing, nuclear export, degradation and translation. Accumulated evidence suggests that m(6)A modification plays a crucial role in the pathogenic mechanism and malignant progression in non-small cell lung cancer (NSCLC), including cell survival, proliferation, migration, invasion, tumor metastasis and drug resistance. Moreover, the expression of m(6)A and its related proteins are dysregulated in clinical samples and circulating tumor cells (CTCs) of lung cancer patients, indicating that m(6)A modification may serve as a novel potential biomarker for the diagnosis and prognosis of lung cancer. In this review, by summarizing a great number of recent reports related to m(6)A's function and its modulators, we aim to provide a new insight on the early diagnosis and drug development in NSCLC therapy.